Short-term evaluation of cardiac morphology, function, metabolism and structure following diagnosis of adult-onset growth hormone deficiency. (June 2019) - De Cobelli, Francesco; Rossini, Alessandro; Esposito, Antonio; Canu, Tamara; Manzoni, Giuseppina; Del Maschio, Alessandro; Rubinacci, Alessandro; Sirtori, Marcella; Losa, Marco; Lanzi, Roberto; Perseghin, Gianluca
Abstract: Objective: The impact of growth hormone (GH) deficiency of the adult on cardiovascular function remains only partially elucidated. Purpose of this study was to test cardiac function in adult GH deficient patients using cardiac magnetic resonance (CMR). Design: Cardiac magnetic resonance (CMR) techniques, including cardiac 31 P MR spectroscopy and evaluation of gadolinium late-enhancement, were applied to assess simultaneously, in a cross-sectional fashion, morphological, functional, metabolic, and structural parameters of the left (LV) and right ventricle (RV) in 15 patients with adult onset GH deficiency. Fifteen healthy individuals served as controls. Results: In GH deficient patients LV systolic function (EF%: 61 ± 1.7 vs 62.1 ± 0.8; p  = .44) was not different in spite of a lower LV mass (83.2 ± 5.3 vs 145.3 ± 11.9 g; p  = .001), a subclinical impairment of diastolic function (E/A peak ratio: 1.6 ± 0.2 vs 2.1 ± 0.2 p  = .05), and a trend for lower PCr/ATP ratio (2.1 ± 0.8 vs 2.3 ± 0.1 p  = .07). The RV showed reduced chamber size (end diastolic volume 123.8 ± 9 vs 147.9 ± 7.6 mL; p  = .021) with preserved mass. No structural alterations of the LV and RV at late-enhancement were detected in these patients. Conclusions: GH deficient patients represent a unique model of reduced LV myocardial mass in which major structural and metabolic alterations are lacking. Mal-adaptive mechanisms developing in the long term in response to GH deficiency and more severely affecting the LV remain to be elucidated. Highlights: Adult-onset GH deficient patients are an atypical model of cardiac impairment. Reduced left-ventricle myocardial mass with a normal global cardiac function No major alterations of heart structure or LV energy metabolism Potential long-term detrimental consequences need to be further elucidated.